Derin Yapı-Yüzey Yapı. - Erenoğlu, Dilek (Türkoloji Kültürü, 2008)
Humanbeing, covering or making it visible; use the languagewhich makes him meaningful, as a device of reflection. Themeaning of the sentence which is a sign of the integrity of thelanguage, were just a meaning of the words which it consists of;knowing the words one by one would be enough to determine themeaning of that sentence. Determining the meaning of the sentencecorrectly,can only be possible with its surface structures and deepstructures. Each of the adult speaker, has the ability of creating anew sentence in his or her own language which hasn't been saidbefore. The listeners also has the ability of understanding of this sentence even if they had not heard it before. This occurs thanks tothe structures of the meaning which the speaker and listener hadagreed on before, without knowing each other. In this study designates the descriptisons about surfacestructure and deep structure extensively and with their examples.